United States and European Union Evolving Approaches in Southeast Asia: Moving Closer to Convergence or Divergence?. Issue 2 (August 2019) - Pennisi di Floristella, Angela
With the launch of Barack Obama's strategic rebalance to Asia-Pacific, there has been a widening of the United States' military, economic, and diplomatic presence in the Southeast Asian region. Likewise, it is clear that Southeast Asia is currently a region of relevant interest for both the United States and the European Union (EU). Surprisingly, however, up to the present, a systematic comparison of their approaches in the region has been largely lacking. To fill this void, this article compares US and EU interests, strategies, and main instruments of cooperation in Southeast Asia. Special attention is paid to the main developments that occurred in the United States, from Obama's announcement of a strategic rebalance to Asia-Pacific to Donald Trump's National Security Strategy, and in the EU, with the release there of the 2012 "Updated East Asia Policy Guidelines." Examining whether the EU and the United States are moving towards a greater convergence of intent is of crucial importance for identifying opportunities for the further development of the transatlantic relationship in Southeast Asia. This article argues, though, that despite some apparent common traits in the US's and the EU's intentions, their strategies and instruments ultimately differ substantially – reflecting divergent paths. This creates crucial impediments to any further development of transatlantic cooperation in Southeast Asia.